Antecedents of Thai Consumer Bottled Water Brand Loyalty (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Globally, consumers are now purchasing 100 billion gallons of bottled water each year, with bottled water the number one consumer beverage. Furthermore, Thailand is now ranked 7th in the world in bottled water consumption. Understanding the economic and health importance of this data, the authors selected the top six bottled water brands in Thailand to investigate the opinions of 489 consumers on what contributes to their brand loyalty (BL). From the use of LISREL 9.1 software, an SEM analysis determined that BL was most affected by corporate social responsibility (CSR), brand image (BI), customer satisfaction (CS), and brand trust (BT).